The Extreme Searcher's Guide to Web Search Engines: A Handbook for the Serious Searcher. 2nd Edition - Hock, Randolph (Information Today, Inc, 2001)
This book aims to facilitate more effective and efficient use of World Wide Web search engines by helping the reader: know the basic structure of the major search engines; become acquainted with those attributes (features, benefits, options, content, etc.) that search engines have in common and where they differ; know the main strengths and weaknesses of the major search engines; and pick up some tips, tricks, and techniques that can contribute to more effective and easier searching. Chapter 1 discusses search engines in general, including a brief history, how search engines are put together, the databases behind the databases, portal features, components of a typical search engine home page, what to realistically expect from these services, subjects/areas covered by search engines, update frequency, typical retrieval and ranking factors, benchmarks, and overlap of retrieval between engines. Chapter 2 covers common searching options, including selection of what is to be searched, Boolean logic, truncation, phrase and proximity searching, name searching, field searching, requesting similar records, output options, international versions, and portal features. Chapters 3-10 present profiles of the following selected search engines: AltaVista, Excite, Fast Search, Google, HotBot, Lycos, Northern Light, and Yahoo. Chapter 11 describes meta-search tools, including Dogpile, ixquick, MetaCrawler, ProFusion, and Search.com. Chapter 12 discusses other search engines and keeping up. (Includes a glossary and an index.) (MES)